THE EFFECT OF SPINACH FLOUR TO THE ACCEPTANCE AND NUTRIENT CONTENT OF SUBSTITUTION OYSTER MUSHROOM DRIED NOODLES - Rahmawati, Rahmawati; Wahyuni, Fitri; Hariati, Niken Widyastuti (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
Dried noodles are fresh noodles to instantly drained its water levels reached up to 8-10%. The presence of the excess, so that the noodles started to preferred even become culture an alternative food substitute for rice. Raw materials of making noodles in general is flour made from wheat that must be imported. Substitution and fortification partial with other materials is one form of innovation as an effort reduce dependence of flour such as oyster mushrooms and spinach flour. The purpose of this research was to determine the acceptability and nutrient content of dried noodles subsititution of oyster mushroom flour with fortification of spinach flour. Randomized Block Design (RBD) was used in this experiment with four levels of treatment with a mixture of fortification flour formula, namely: F1 (5%), F2 (10%), F3 (15%), F5 (20%) that added in dried oyster mushrooms noodles (70:30)%. The acceptability rated from organoleptic conducted on semi trained panelists were as many as 30 students and the levels of nutrient content from the results of the laboratory test used the proximate and spectrophotometry. Based on organoleptic and results weighting values, the formula 5 had received higher panelists from other formula with a score of 59.9. Laboratory result showed protein 18.03 g, fat 8.01 g, 6.60 g water, ash 6.56 g, fiber 34.90 g, carbohydrates 19.25 g, and 015 mg of iron. The noodle product with proportion of wheat and oyster mushrooms flour has a good acceptability and higher nutrient content compared to commercial dried noodles in general.Dried noodles are fresh noodles to instantly drained its water levels reached up to 8-10%. The presence of the excess, so that the noodles started to preferred even become culture an alternative food substitute for rice. Raw materials of making noodles in general is flour made from wheat that must be imported. Substitution and fortification partial with other materials is one form of innovation as an effort reduce dependence of flour such as oyster mushrooms and spinach flour. The purpose of this research was to determine the acceptability and nutrient content of dried noodles subsititution of oyster mushroom flour with fortification of spinach flour. Randomized Block Design (RBD) was used in this experiment with four levels of treatment with a mixture of fortification flour formula, namely: F1 (5%), F2 (10%), F3 (15%), F5 (20%) that added in dried oyster mushrooms noodles (70:30)%. The acceptability rated from organoleptic conducted on semi trained panelists were as many as 30 students and the levels of nutrient content from the results of the laboratory test used the proximate and spectrophotometry. Based on organoleptic and results weighting values, the formula 5 had received higher panelists from other formula with a score of 59.9. Laboratory result showed protein 18.03 g, fat 8.01 g, 6.60 g water, ash 6.56 g, fiber 34.90 g, carbohydrates 19.25 g, and 015 mg of iron. The noodle product with proportion of wheat and oyster mushrooms flour has a good acceptability and higher nutrient content compared to commercial dried noodles in general.